Antigenic Challenge Influences Epigenetic Changes in Antigen-Specific T Regulatory Cells - Iwaszkiewicz-Grzes, Dorota; Piotrowska, Magdalena; Gliwinski, Mateusz; Urban-Wójciuk, Zuzanna; Trzonkowski, Piotr (Frontiers in Immunology, 2021)
Background Human regulatory T cells (Tregs) are the fundamental component of the immune system imposing immune tolerance via control of effector T cells (Teffs). Ongoing attempts to improve Tregs function have led to the creation of a protocol that produces antigen-specific Tregs, when polyclonal Tregs are stimulated with monocytes loaded with antigens specific for type 1 diabetes. Nevertheless, the efficiency of the suppression exerted by the produced Tregs depended on the antigen with the best results when insulin β chain peptide 9-23 was used. Here, we examined epigenetic modifications, which could influence these functional differences. Methods The analysis was pefromed in the sorted specific (SPEC, proliferating) and unspecific (UNSPEC, non-proliferating) subsets of Tregs and Teffs generated by the stimulation with monocytes loaded with either whole insulin (INS) or insulin β chain peptide 9-23 (B:9-23) or polyclonal cells stimulated with anti-CD3/anti-CD28 beads (POLY). A relative expression of crucial Tregs genes was determined by qRT-PCR. The Treg-specific demethylated region (TSDR) in FoxP3 gene methylation levels were assessed by Quantitative Methylation Specific PCR (qMSP). ELISA was used to measure genomic DNA methylation and histone H3 post-translational modifications (PTMs). Results Tregs SPECB:9-23 was the only subset expressing all assessed genes necessary for regulatory function with the highest level of expression among all analyzed conditions. The methylation of global DNA as well as TSDR were significantly lower in Tregs SPECB:9-23 than in Tregs SPECINS. When compared to Teffs, Tregs were characterized by a relatively lower level of PTMs but it varied in respective Tregs/Teffs pairs. Importantly, whenever the difference in PTM within Tregs/Teffs pair was significant, it was always low in one subset from the pair and high in the other. It was always low in Tregs SPECINS and high in Teffs SPECINS, while it was high in Tregs UNSPECINS and low in Teffs UNSPECINS. There were no differences in Tregs/Teffs SPECB:9-23 pair and the level of modifications was low in Tregs UNSPECB:9-23 and high in Teffs UNSPECB:9-23. The regions of PTMs in which differences were significant overlapped only partially between particular Tregs/Teffs pairs. Conclusions Whole insulin and insulin β chain peptide 9-23 affected epigenetic changes in CD4+ T cells differently, when presented by monocytes. The peptide preferably favored specific Tregs, while whole insulin activated both Tregs and Teffs.